Drugs, moral panics and the dispositive. (December 2018) - Bennett, Cary
The concept of 'moral panics' continues to be used as a framework for analysing the causes, structures and functions of social and political crises. Nonetheless, as an analytical tool, such a framework is limited in its capacity to explain the ongoing and interconnected relationships between drugs and society. Drawing first on an interdiscursive and intertextual framework, the field of analysis is broadened to consider how recent drug panics in Australia depend upon, signify and condense wider social and historical anxieties around drugs and other social problems. However, such an approach also has its limitations given that the play of intertextuality is conditioned by relations of power at the level of what Foucault calls a 'dispositive', a historically contingent configuration that strategically orientates our responses to the problem. Three dispositional drug-related prototypes are considered and how they work together to shape, reinforce and condition the drug problem and our responses to it.